Kvantna teleportacija - Močan Kozina, Ana (Matrika, 2020)
This article talks about Quantum Teleportation - transfer of information across an arbitrary distance using quantum entanglement. In the Introduction, the EPR paradox is presented, along with quantum entanglement and the resolution of the paradox with Bell's inequality. Later on, the theory of quantum teleportation is explained and some of the experimental accomplishments are presented. First, the first successful quantum teleportation experiment is presented, then the so called Vienna experiment, where they teleported photons across 800 meter tunnel beneath the river Danube, and last, the so called Chip to Chip teleportation, teleportation between two computer chips, is presented. In conclusion, some plans and ideas for the future are discussed.
Keywords: Bellova neenakost; Bell's inequality; kvantna prepletenost; kvantna teorija; quantum entanglement; quantum theory